Introduction to celebrating Latin American talent in chemistry. Issue 63 (17th December 2021) - Merino, Gabriel; Fernández-Herrera, María A.; Soler-Illia, Galo J. A. A.; Zarbin, Aldo J. G.; Zuin, Vânia G.; Chamorro, Eduardo; de Oliveira, Luciana G.; Mesko, Márcia Foster; Fraga, Cesar; Ibarra Alvarado, Ilich A.; Dupont, Jairton; Nogueira, Ana Flávia; et al.
Abstract : In celebration of the excellence and breadth of Latin American research achievements across the chemical sciences, we are delighted to present an introduction to the themed collection, Celebrating Latin American talent in chemistry.